Resíduo de madeira em Presidente Prudente: um estudo sobre a viabilidade ecológica e comercial na fabricação de briquetes - Donato, Claudio José (2020)
The inadequate disposal of waste generated during the mechanical processing of wood has been causing a series of environmental problems. Awareness regarding storage, storage and disposal is necessary in order to avoid disposal in nature causing soil contamination. Therefore, it is necessary to develop techniques to take advantage of them in order to reduce the pressure on native forests. One of the techniques is briquetting, which consists of compacting wood waste by a mechanical press producing the briquette. One of the legacies of this research is to contribute to the scarce studies on the subject, the lack of knowledge and awareness of this technique by society as a system for the reuse of wood debris and its importance to the environment. Wood residues are classified as class I solid from industry and civil construction. The objective of the research is to discuss the impact impact on the environment by the advanced disposal of wood waste (sawdust and wood shavings, tree pruning and pruning), and to evaluate the environmental and commercial viability of reusing these residues in the manufacture of briquettes in the city Presidente Prudente located west of the state of São Paulo. The methodology was divided into bibliographic research using all theoretical framework to understand what the studies carried out debate about the subject and field research with the cataloging of the companies that generate the residues and the quantification of the residues transmitted for verification if it is viable to use his in the manufacture of briquettes and, finally, the discussion and analysis of the collected data. The results of the research point to the use of the studied residues as a source of renewable energy, briquettes, contributing to the generation of jobs, reduction of the visual source both in the logging yards and in the places of inappropriate discharges scattered throughout the city